Optimizing Technology in Child Counseling: YouTube Kids as Islamic Education - Wahyu Pambudi, Giri; Muh. Nur Rochim Maksum; Hafidz (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The rapid development of digital technology has had a significant impact on family life, particularly in the education and upbringing of children. Shifting interaction patterns from physical to virtual requires parents and educators to adopt new, adaptive approaches based on digital literacy. This study aims to disseminate YouTube Kids as an informal educational medium that supports the guidance and development of Islamic character in children. Using a literature review method and a descriptive qualitative approach, this study explains the positive impacts and risks of digital content, particularly Islamic content circulating on the YouTube Kids platform. The study results indicate that although this platform offers significant opportunities for conveying moral and religious values in an engaging and interactive manner, there are serious challenges related to content filtering, the pedagogy used, and the psychological risks resulting from fear-based narratives. Therefore, the active role of parents and educators as wise curators and digital mentors is needed. This study recommends a synergy between curated digital education and positive Islamic pedagogical principles to create a safe, enjoyable learning environment and build children’s character holistically.